Inherent Optical Properties based Vulnerability Assessment of Euphotic Zone Compression in peatland influenced Southeast Asian coastal waters - Sanwlani, Nivedita; Wong, Elizabeth Wing-See; Morgan, Kyle; Liew, Soo Chin; Martin, Patrick (Frontiers in Marine Science, 2022)
Underwater light availability is a crucial aspect for the ecological functioning of shallow water bodies. Light extinction from terrestrial inputs is a growing threat to these coastal habitats. The blended quasi-analytical algorithm (QAA) was extended for the derivation of colored dissolved organic matter (CDOM) absorption coefficient along with other inherent optical properties (IOPs) from satellite observations for Southeast Asian waters. The contribution of these IOPs to diffuse attenuation of light (Kd) and penetration depth (Zd) was investigated. A vulnerability assessment was performed to identify locations potentially threatened by poor light quality in Southeast Asian waters. Advection of peatland-influenced Sumatran coastal waters rich in organic matter (ag(400nm): 1.0-2.0m-1) and sediments (bbp(400nm): 0.5-1m-1) drive the spatial heterogeneity of Sunda shelf seawater. Photic zone depth, Zd(490nm), is year-round restricted to ≤5m for critically vulnerable Sumatran coastal waters (vulnerability index, VI>0.8). This critically vulnerable state is further extended towards the southern Malacca Strait, influencing the eastern Singapore Strait from June to September. The areas harbouring marine ecosystems in the shelf waters attain a higher threshold (VI=0.6-0.8), constraining the photosynthesis to depths ≤10m. A transformation of central Malacca Strait from not vulnerable (VI<0.2) to highly vulnerable (VI=0.6-0.8) state during the season indicates poor light conditions. Further intensiﬁcation of CDOM and sediments in these water columns, therefore, constitute a clear risk of an increasing lack of light, which may have damaging effects on the functioning of coastal habitats. This study underscores the need for a complete ecological risk assessment for Southeast Asia to aid in the effective management of marine ecosystems.